Improving multi-view video fusion and model generalization in pig behavior monitoring with teacher–student semi-supervised learning - Shuo Wan; Junkai Li; Feiyue Xue; Tao Han; Ying Sha; Li Qin (Computers and Electronics in Agriculture, 2026)

Accelerating large-scale plane-wave hybrid functional calculations via low-rank approximations and high-performance computing on the Sugon supercomputer - Yufan Yao; Junwei Feng; Lingyun Wan; Shizhe Jiao; Jielan Li; Junshi Chen; Hong An; Xinming Qin; Wei Hu; Jinlong Yang (Computer Physics Communications, 2026)

Multi-target protective effects of Pterostilbene against BPA-induced reproductive toxicity revealed by integrative network pharmacology and in vivo validation - Ruixue Li; Ali Danish Alvi; Mei Chen; Hao Guo; Clara Appiah; Wenjing Qin; Jiahang Wan; Xuanyan Liu; Ye Zhao (Tissue and Cell, 2026)

Functional characterization of a plant germacrene D-4-ol synthase enabling the production of bioactive α-cadinol and τ-muurolol under changed catalysis conditions - Shao-Jun Cheng; Shi-Jie Liu; Wan-Jun Liang; Qin-Qin Shen; Zhong-Zhu Yuan; Zong-Hua Xiao; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Feasibility-enhanced and cluster-guided optimization for coordinated hydro-wind-photovoltaic dispatch under cross-regional power delivery - Zixuan Liu; Yuliang Han; Songyan Hu; Wan Liu; Wenjing Xiao; Xutong Sun; Qin Shen; Li Mo (Journal of Cleaner Production, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Effects of myo-inositol hexakisphosphate on the Fe(II)-catalyzed transformation of Al-substituted ferrihydrite: A concentration-dependent mechanism and implications for phosphorus geochemical cycling - Yuan Qiu; Lisong Ma; Biao Wan; Xinran Liang; Shuai Lan; Guanjie Jiang; Yang Li; Qin Zhang; Yupeng Yan (Chemical Geology, 2026)

Apicidin is a key virulence determinant of Fusarium asiaticum in wheat-rice cropping systems - Xin Liu; Kainan Li; Jianbo Qiu; Tao Gao; Yi Shi; Guanghui Shen; Yunyun Zhou; Shilong Hu; Xuanlong Ruan; Jingya Wan; Yin-Won Lee; Qin Gu; et al. (Science China Life Sciences, 2026)

Influence of micropile design parameters on slip surface morphology and factor of safety of submarine slopes - Yuke Wang; Zhenjia Qin; Yukuai Wan; Xiaoning Zhang; Kun Hu; Aiguo Li; Qingxi Li (Marine Georesources & Geotechnology, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

The ZxCNIH4-ZxHKT1;1 module responding to external NaCl orchestrates Na+ partitioning in a xerophyte - Jie Huang; Pei-Qin Li; Tian-Qiong Wang; Wan-Peng Bai; Hu-Jun Li; Jin Ke; Yuan-Zhou Pan; Suo-Min Wang (Plant Science, 2026)

1H NMR-guided isolation of ophiobolins from Bipolaris maydis and their bioactivities - Yong Shen; Xiaotian Zhang; Qin Li; Mengru Yu; Yongqi Li; Luosheng Wan; Xing Sun; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Prenatal neonicotinoid insecticide exposure, maternal steroid hormone levels, and precocious puberty in girls: A nested case-control study - Ruijia Li; Ying Li; Miaomiao Yan; Jiahao Li; Xiaoyuan Qin; Ai Gao; Hongxiu Liu; Yuanyuan Li; Shunqing Xu; Peipei Jiang; Yanjian Wan; Wei Xia (Environmental Pollution, 2026)

Genome-wide analysis of HSP70 family in Zygophyllum xanthoxylum and its heat stress response in Arabidopsis - Wan-Peng Bai; Tian-Qiong Wang; Qin Liu; Hu-Jun Li; Li Wei; Suo-Min Wang (Plant Cell Reports, 2026)

The multifunctional applications and mechanisms of biochar in wastewater treatment: From adsorption to catalysis - Zhikai Qin; Yue Yuan; Min Xu; Chunli Wan; Min Li; Yutong Duan; Changyong Wu (Journal of Environmental Management, 2026)

Chlorella GY-D12-biochar composite for lead and cadmium removal from wastewater - Sana Irshad; Asad Nawaz; Xiyao Liu; Shiyang Wu; Sajad Ali; Yi Peng; Yixin Wan; Xu Liao; Zunhua Li; Meifeng Wang; Zuodong Qin (Journal of Environmental Chemical Engineering, 2026)

The Role of Atlantic Multidecadal Oscillation in Decadal Summer Temperature Variability Over the Tibetan Plateau in Observations and Pacemaker Simulations - Yanfeng He; Minhua Qin; Chuntao Yu; Huiting Feng; Hongwei Chen; Ming Li; Tao Wang; Min Wan; Shanlei Sun; Wenjian Hua (International Journal of Climatology, 2026)
Previous studies have suggested that internal oceanic modes such as the Interdecadal Pacific Oscillation (IPO) and Atlantic Multidecadal Oscillation (AMO) have significant effects on the decadal temperature variability over the Tibetan Plateau (TP). However, assessments of decadal variability are very sensitive to the length of study periods. Thus, the dominant factors regulating the decadal temperature variations over the TP and the associated mechanisms have not been clearly identified. This study utilised long‐term temperature observations, global reanalysis and climate model simulations to examine the decadal variations and the underlying mechanisms of surface air temperature (SAT) over the TP during boreal summer from 1901 to 2020. Results show that there exist decadal variations in summer TP SAT, with warm periods during 1929–1960 and 1999–2020 and cold periods during 1901–1928 and 1961–1998. It has also been found that the decadal changes in summer TP SAT are closely associated with the AMO. In contrast, TP SAT has a weak relationship with the IPO during 1901–2020. North Atlantic pacemaker simulations further show a zonal wave train pattern propagating from the North Atlantic to East Asia, which triggers anomalous anticyclonic circulations over the northern TP and Lake Baikal. The regional anticyclonic circulation anomalies over the TP not only weaken the subtropical westerly jet stream but also facilitate the water vapour transport into the TP and further cause local warming over the TP. Our findings elucidate the role of internal climate variability in shaping the decadal variability of summer TP SAT and also help reduce uncertainties in future projections of TP SAT changes.

Improving ignition and combustion of B/KClO4 by introducing polyethylene glycol as a surfactant - Honghong Qin; Wenzhe Ma; Li Ding; Chong Wan; Qingguang Zhu; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Fuel, 2026)

Associations of maternal exposure to nonylphenol and bisphenols with precocious puberty in girls: A nested case-control study - Miaomiao Yan; Yanjian Wan; Ruijia Li; Jiahao Li; Xiaoyuan Qin; Yuanyuan Li; Hongxiu Liu; Shunqing Xu; Qianru Zhou; Sha Huang; Wei Xia (Environmental Research, 2026)

Hemagglutinin-encoded mRNA vaccine confers efficient protection against H3N8 avian influenza virus in mice - Jiayan Wu; Wenjie Jiang; Xingyao Guo; Jingwen Li; Shengnan Wang; Zhimin Wan; Quan Xie; Hongxia Shao; Wei Gao; Aijian Qin; Tuofan Li; Jianqiang Ye (Veterinary Microbiology, 2026)

Urban road network resilience under emergencies: a microscopic simulation framework - Weiping Wang; Yingying Wan; Qian Liu; Hao Liu; Chunhong Li; Saini Yang; Xinjun Lai; Yimeng Liu; Qin Yue (Transportation Research Part D: Transport and Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Genetic characteristics of three duck-original H1N1 influenza A viruses isolated in China - Qiuqi Kan; Xuefeng Yin; Xingyao Guo; Xinran Chu; Jianjun Sang; Xudong Cao; Jixiang Wang; Wenjie Jiang; Zhehong Zhao; Quan Xie; Tuofan Li; Hongxia Shao; et al. (Veterinary Microbiology, 2026)

Deciphering thermal behaviors of Qingchuan bitumen: Effects of atmosphere, heating rate, sample weight, kerogen, and clay minerals - Xianghui Zhang; Yuanyu Kou; Qin Liu; Huan Yang; Wei Hu; Xiangqi Leiyu; Hailong Wan; Wenling Yang; Xinyu Li; Junjie Wang; Ling Wang; Qian Feng (Fuel, 2026)

Cofilin 1-138 Promotes Mitochondrial Dysfunction and Synaptic Degeneration in Parkinson’s Disease - Di Zhang; Yidan Chen; Haibo Zhang; Hongyang Liu; Dan Wang; Qin Li; Hualan Qin; Yue Wan; Mingmin Yan (Molecular Neurobiology, 2026)

Correction: Lei et al. Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus. Fishes 2024, 9, 452 - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2025)
In the original publication [...]

A novel recombinant serotype 4 fowl adenovirus efficiently protects both serotype 4 and 11 fowl adenovirus - Shi Liu; Ye Tang; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Quan Xie; Wei Gao; Jianqiang Ye (Veterinary Microbiology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Characterizing the impact of lactic acid bacteria-fermented vegetable juice on microbial assemblage and quality of pickled suancai - Kaidi Hu; Jing Li; Min Zhang; Yizhuo Wan; Yankang Yang; Jingyi Ren; Zerong Jin; Wen Wang; Yunxiao Wan; Qisheng Zhang; Dongdong Wang; Weiqin Deng; et al. (Food Research International, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Green manure species synergize with organic fertilization to enhance soil nutrient–microbial interactions and wheat productivity in oasis drip–irrigated systems - Liyang Cheng; Hao He; Shuai Li; Mengmeng Yu; Tingting Wan; Jie Qin; Chunyan Li; Junhua Li (Field Crops Research, 2025)

Amino acid-induced supramolecular assembly defective carbon nitride for efficient photocatalytic CO2 reduction - Rui Li; Liting Lai; Si Li; Shipeng Wan; Wenbei Jia; Yu Han; Ruixuan Chu; Qin Zhong; Zhaoxiang Zhong (Chemical Engineering Journal, 2025)

Fabrication of Plantaricin FB-2 loaded chitosan/agar coatings: Enhancing antimicrobial activity and prolonging fresh pork shelf life - Shuang Yu; Qin Chen; Sivakumar Manickam; Yuxun Li; Mengyao Zhang; Xiaohu Luo; Jiali Xing; Ying Wan; Dan Ouyang; Jian Shen; Yanan Liu (International Journal of Food Microbiology, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Diversity, evolution, and gene regulation of endogenous retroviruses in eight important poultry species - Ali Shoaib Moawad; Amaal Omara; Zhimin Wan; Quan Xie; Hongxia Shao; Aijian Qin; Tuofan Li; Jianqiang Ye (Veterinary Microbiology, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Erosion processes of lahar travelling on volcanic sediments: Insights from the physical and numerical modeling - Shengwu Qin; Jiangfeng Lv; Shuangshuang Qiao; Junjun Chen; Feng Wan; Jingyu Yao; Guangjie Li; Lingshuai Zhang (CATENA, 2025)

Sex-dependent effects of heat exposure on the middle ear health in mice - Jie Li; Wenjun Fan; Xiangyi Yuan; Teng Wan; Li Qin; Lu Zhang; Tong Hou; Cuiqing Liu; Ran Li (Journal of Thermal Biology, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Study on sand column collapse mechanisms through optical frequency domain reflectometry and particle image velocimetry - Dao-Yuan Tan; Ning Ma; Yong-Qin Li; Hong-Hu Zhu; Lei Gao; Du-Min Yan; Wan-Huan Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

A novel, ridged enlarging lateral space drip irrigation pattern (ReDiP) for high- yield and WUE spring wheat in Xinjiang, China - Liulong Li; Zijian Wang; Wenliang Wan; Zhaofeng Li; Jian Cai; Qin Zhou; Mei Huang; Yingxin Zhong; Xiao Wang; Dong Jiang (Field Crops Research, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

Trait segregation and growth characteristics of the F2 generation hybrids between Crassostrea dianbaiensis and C. iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture International, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

Adsorption–Desorption and Interfacial Distribution Characteristics of Petroleum Hydrocarbons in Soil Systems - Ao Yang; Yong-Tao Li; Jian-ying Xiao; Wan-Ying Du; Xi Li; Qin Sui; Yu-Qin Wang (Water, Air, & Soil Pollution, 2025)

Offspring performance of backcrossing between hybrid line of Crassostrea dianbaiensis ♀ × Crassostrea iredalei ♂ and their parental species - Jiangwei Li; Yanping Qin; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Preferred crystal plane growth orientation induced by low-energy ions for highly reversible zinc anodes - Guanzhong Wang; Xiyan Bao; Xiaofang Wang; Xize Chen; Wei Lai; Di Wu; Chen Zhang; Lin Gao; Minglei Cao; Xingxing Li; Qin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Growth performance of two brackish oysters (Crassostrea iredalei and Crassostrea dianbaiensis) and their hybrids in subtropical sea area - Jiangwei Li; Ying Pan; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Shengyong Li; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture, 2025)

Effects of salt ions and pH on deamidated soybean protein hydrogels formation: Molecular structure, thermal aggregation and network - Tang-Hao Li; Yao-Qin Yang; Gao-Shang Wang; Ding-Yang Lv; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Chemistry, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Designer electron-reservoir single-atom electrocatalyst for efficient carbon dioxide reduction - Wanli Yi; Changsheng Hou; Renyi Li; Yinji Wan; Xuan Zhang; Bing Ma; Wenchao Hu; Shenghui Han; Mulin Qin; Limeng Sun; Qian Wang; Yonggang Wang; et al. (Chemical Engineering Journal, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Corrigendum to “Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei” [Aquaculture, Volume 595, Part 2, 30 January 2025, 741656] - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

First successful inducing gynogenesis in Crassostrea angulata by inactivated tetraploid Crassostrea gigas sperm - Weitao Wan; Yanping Qin; Jinhui Wu; Haitao Ma; Chao Yue; Shengyong Li; Jiangwei Li; Zhongyu Wang; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; et al. (Aquaculture, 2025)

Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

Evaluating the impact of dermal absorption on internal doses of dechlorane plus in Chinese e-waste recycling employees - Yao-Yuan Wan; Xiao-meng Cheng; Xing-Hong Li; Feng-Shuang Wang; Yuan-Yuan Li; Jing Li; Zhan-Fen Qin (Chemosphere, 2024)

Highly efficient recovery of gold by thermally modified pyrite and its mechanism - Yuhong Fu; Can Wu; Qin Liu; Shanshan Li; Sen Li; Shuai Zhang; Quan Wan (Minerals Engineering, 2024)

Surface in situ Co-Mn modification over LaMnO3 perovskite with enhanced activity for ethane combustion - Peng Zhao; Jingwei Liu; Wei Zhu; Jie Meng; Zhuang Li; Jinwei Qin; Xiaohui Wang; Haiqin Wan; Chao Yao; Lin Dong (Journal of Environmental Chemical Engineering, 2024)

Transcriptomic Analysis of Non-Specific Immune Responses in the Rice Field Eel (Monopterus albus) Infected with Pallisentis (Neosentis) celatus - Qin Lei; Xiaoling Li; Hao Wu; Yiwen Wan; Yukun Xie; Jinwei Gao; Wenwen Suo; Ming Zeng; Lingli Liu; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Parasitic infestations present significant threats to the physiological health and ecological stability of aquatic species, frequently compromising immune defenses and elevating mortality rates. This study was conducted to elucidate the non-specific immune responses induced by Pallisentis (Neosentis) celatus infection in Monopterus albus, with a focus on intestinal histopathology and transcriptome gene expression. A histopathological examination revealed minor alterations in intestinal villi under low-level infection. A transcriptome analysis, performed using Illumina sequencing technology, identified 347 upregulated and 298 downregulated genes involved in critical biological pathways, such as lipid metabolism, immune responses, and the regulation of inflammatory processes. GO and KEGG analyses indicated the upregulation of immune-related pathways, including the RIG-I-like and IL-17 signaling pathways, highlighting a robust intestinal immune response. Conversely, the complement pathway was found to be downregulated, with significant suppression of C9, suggesting that the parasite may engage in immune evasion. Fluorescein-labeled C9 antibody assays confirmed reduced complement C9 levels in the infected tissues. A real-time PCR analysis identified the differential expression of eight genes, including C5, maats1, CFI, and gmnc, which were consistent with the sequencing results. These findings suggest that Pallisentis (Neosentis) celatus infection compromises intestinal health, induces inflammation, and activates non-specific immune responses in Monopterus albus. However, Pallisentis (Neosentis) celatus appears to evade the host immune response by suppressing the activation of complement components, thereby facilitating its reproductive parasitism.

Parental exposure to acrylamide disrupts sphingolipid metabolism and impairs transgenerational neurodevelopment in zebrafish (Danio rerio) offspring - Anli Wang; Yingyu Huang; Xiaoran Song; Jia Zeng; Li Zhu; Binjie Wang; Yuanzhao Wu; Zhongshi Xu; Ruonan Zheng; Yazhou Qin; Jiye Wang; Weixuan Yao; et al. (Science of The Total Environment, 2024)

Enhanced foaming and surface properties of soybean glycinin via hydrothermal treatment at acidic conditions - Lang Qin; Tanghao Li; Jian Guo; Jinmei Wang; Zhili Wan; Xiaoquan Yang (Food Hydrocolloids, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Enhancing energy release and controlled combustion of B-based MICs by the synergistic effect between polyvinyl pyrrolidone and nitrocellulose - Chong Wan; Suhang Chen; Xinglong Liu; Yushu Xiong; Zhao Qin; Jianbin Li; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

Closed-loop recyclable wood-plastic composite as a sustainable alternative to wood: A solution for utilizing wood waste and promoting carbon sequestration - Shuang-Xi Hou; Chun-Yan Zhao; Wan-Ting Xiong; Jie Zhang; Mao-Qin Li; Guo-Qiang Tian; Gang Wu; Si-Chong Chen; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Corrigendum to “Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding” [Aquaculture 563 (2023) 738910] - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Successive selection responses of tetraploid Crassostrea angulata: Comparison of growth, survival, sex ratio and ploidy composition between selected and unselected groups - Yanping Qin; Weitao Wan; Jiangwei Li; Chao Yue; Zhongyu Wang; Qinggan Xing; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Enhanced in-situ zero-valent iron activated persulfate oxidation with electrokinetics for the remediation of petroleum hydrocarbon contaminated soil - Yong-Tao Li; Qin Sui; Xi Li; Yu-Qin Wang; Xin-Yue Liu; Hao Liu; Wan-Ying Du (Journal of Environmental Chemical Engineering, 2024)

Formation of a transparent soy protein hydrogel: Controlled thermal aggregation of protein using glutaminase - Tang-Hao Li; Yao-Qin Yang; Ding-Yang Lv; Gao-Shang Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2024)

High Homocysteine-Thiolactone Leads to Reduced MENIN Protein Expression and an Impaired DNA Damage Response: Implications for Neural Tube Defects - Baoling Bai; Chunlei Wan; Zonghui Xiao; Dan Li; Lingyun Liu; Kexin Zhang; Ting Zhang; Qin Zhang (Molecular Neurobiology, 2024)
DNA damage is associated with hyperhomocysteinemia (HHcy) and neural tube defects (NTDs). Additionally, HHcy is a risk factor for NTDs. Therefore, this study examined whether DNA damage is involved in HHcy-induced NTDs and investigated the underlying pathological mechanisms involved. Embryonic day 9 (E9) mouse neuroectoderm cells (NE4C) and homocysteine-thiolactone (HTL, active metabolite of Hcy)-induced NTD chicken embryos were studied by Western blotting, immunofluorescence. RNA interference or gene overexpression techniques were employed to investigate the impact of Menin expression changes on the DNA damage. Chromatin immunoprecipitation-quantitative polymerase chain reaction was used to investigate the epigenetic regulation of histone modifications. An increase in γH2AX (a DNA damage indicator) was detected in HTL-induced NTD chicken embryos and HTL-treated NE4C, accompanied by dysregulation of phospho-Atr-Chk1-nucleotide excision repair (NER) pathway. Further investigation, based on previous research, revealed that disruption of NER was subject to the epigenetic regulation of low-expressed Menin-H3K4me3. Overexpression of Menin or supplementation with folic acid in HTL-treated NE4C reversed the adverse effects caused by high HTL. Additionally, by overexpressing the Mars gene, we tentatively propose a mechanism whereby HTL regulates Menin expression through H3K79hcy, which subsequently influences H3K4me3 modifications, reflecting an interaction between histone modifications. Finally, in 10 human fetal NTDs with HHcy, we detected a decrease in the expression of Menin-H3K4me3 and disorder in the NER pathway, which to some extent validated our proposed mechanism. The present study demonstrated that the decreased expression of Menin in high HTL downregulated H3K4me3 modifications, further weakening the Atr-Chk1-NER pathway, resulting in the occurrence of NTDs.

Feasibility exploration and comparative analysis of interspecific hybridization between Crassostrea hongkongensis and Crassostrea dianbaiensis - Jiangwei Li; Yanping Qin; Zhongli Peng; Weitao Wan; Chao Yue; Zhongyu Wang; Haitao Ma; Qinggan Xing; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2024)

Methanogenic biodegradation of thermoplastic poly(vinyl alcohol) films produced by two manufacturing processes in enrichment cultures - Ming-Le Ji; Yi-Fan Liu; Yu Bai; Zhen Hu; James H. Wang; Jia-Yi Li; Wan-Qi Qin; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Yingcheng Li; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

Response of soil aggregate-associated fertility and microbial communities to afforestation in the degraded ecosystem of the Danjiangkou Reservoir, China - Peng Chen; Li Wang; Jun-Ya Li; Wenjie Wan; Run-Qin Zhang; Yi Liu; Zhi-Guo Li (Plant and Soil, 2024)

Plant diversity decreases greenhouse gas emissions by increasing soil and plant carbon storage in terrestrial ecosystems - Pengfei Dang; Miaomiao Zhang; Xinli Chen; Michel Loreau; J. Emmett Duffy; Xin'e Li; Shuyue Wen; Xiaoqing Han; Lechen Liao; Tiantian Huang; Chenxi Wan; Xiaoliang Qin; et al. (Ecology Letters, 2024)
The decline in global plant diversity has raised concerns about its implications for carbon fixation and global greenhouse gas emissions (GGE), including carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 ). Therefore, we conducted a comprehensive meta‐analysis of 2103 paired observations, examining GGE, soil organic carbon (SOC) and plant carbon in plant mixtures and monocultures. Our findings indicate that plant mixtures decrease soil N 2 O emissions by 21.4% compared to monocultures. No significant differences occurred between mixtures and monocultures for soil CO 2 emissions, CH 4 emissions or CH 4 uptake. Plant mixtures exhibit higher SOC and plant carbon storage than monocultures. After 10 years of vegetation development, a 40% reduction in species richness decreases SOC content and plant carbon storage by 12.3% and 58.7% respectively. These findings offer insights into the intricate connections between plant diversity, soil and plant carbon storage and GGE—a critical but previously unexamined aspect of biodiversity–ecosystem functioning.

Remediation of petroleum hydrocarbon contaminated soils by nZVI coupled with electrokinetic activation of persulfate - Yong-Tao Li; Yu-Qin Wang; Xi Li; Xin-Yue Liu; Hao Liu; Qin Sui; Wan-Ying Du (Journal of Cleaner Production, 2024)

Identification and characterization of the antifungal proteins from Bacillus velezensis KL-2 to target plant pathogenic fungi - Jinhua Zhou; Junjie Li; Sibao Wan; Zhifeng Yan; Zhen Qin; Haiyan Gao (Food Bioscience, 2024)

Anti-fouling coating with ROS-Triggered On-Demand regulation of inflammation to favor tissue healing on vascular devices - Hui Yan; Lietao Wang; Haoshuang Wu; Yongqi An; Yumei Qin; Zhen Xiang; Huining Wan; Yanfei Tan; Li Yang; Fanjun Zhang; Qing Jiang; Rifang Luo; et al. (Chemical Engineering Journal, 2024)

Growth, survival and reproductive traits of chemical induced and tetraploid-derived triploid Hong Kong oysters (Crassostrea hongkongensis) - Yanping Qin; Weitao Wan; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Early Cretaceous magmatism archives crustal architecture of northern Lhasa Terrane, central Tibetan Plateau - Wan-Li Tang; Feng Huang; Zheng-Wei Qin; Yun-Chuan Zeng; Ji-Feng Xu (Lithos, 2024)

Remediation of diesel contaminated soil by using activated persulfate with Fe3O4 magnetic nanoparticles: effect and mechanisms - Yong-Tao Li; Qin Sui; Xi Li; Xin-Yue Liu; Hao Liu; Yu-Qin Wang; Wan-Ying Du (Environmental Science and Pollution Research, 2024)

Gestational exposure to PM2.5 disrupts fetal development by suppressing placental trophoblast syncytialization via progranulin/mTOR signaling - Yirun Wang; Zhuan Chen; Jie Li; Teng Wan; Renjie Hu; Lu Zhang; Li Qin; Lu Zang; Weijia Gu; Rucheng Chen; Cuiqing Liu; Ran Li (Science of The Total Environment, 2024)

Dynamic changes of zinc chemical speciation and zinc-containing peptides release in oysters (Crassostrea hongkongensis) during enzymatic hydrolysis - Ran Du; Wan Li; Jiawei Li; Shan Zeng; Zhongqin Chen; Jialong Gao; Huina Zheng; Haisheng Lin; Guoping Zhu; Xiaoming Qin; Wenhong Cao (Food Bioscience, 2024)

Cretaceous integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Dangpeng Xi; Guobiao Li; Shijun Jiang; Xin Rao; Tian Jiang; Tianyang Wang; Zuohuan Qin; Yasu Wang; Jianzhong Jia; Muhammad Kamran; Zhongye Shi; Yuyang Wu; et al. (Science China Earth Sciences, 2024)

Phenotypic traits of reciprocal tetraploid hybrids derived from tetraploid Crassostrea gigas and tetraploid Crassostrea angulata - Chao Yue; Yanping Qin; Weitao Wan; Gongpengyang Shi; Shengyong Li; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Enhancing singlet oxygen production of dioxygen activation on the carbon-supported rare-earth oxide nanocluster and rare-earth single atom catalyst to remove antibiotics - Haonan Qin; Meina Guo; Chenliang Zhou; Jiarong Li; Xuequan Jing; Yinhua Wan; Weijie Song; Hongdong Yu; Guan Peng; Zhangwei Yao; Jiaming Liu; Kang Hu (Water Research, 2024)

Plastic film mulching application improves potato yields, reduces ammonia emissions, but boosts the greenhouse gas emissions in China - Yalan Huang; Rongzhu Qin; Huihui Wei; Ning Chai; Yang Yang; Yuling Li; Pingxing Wan; Yufei Li; Wucheng Zhao; Siam Lawawirojwong; Tanita Suepa; Feng Zhang (Journal of Environmental Management, 2024)

Production of single cell protein from brewer’s spent grain through enzymatic saccharification and fermentation enhanced by ammoniation pretreatment - Wan Sun; Zheng Zhang; Xuezhi Li; Xianqin Lu; Guodong Liu; Yuqi Qin; Jian Zhao; Yinbo Qu (Bioresource Technology, 2024)

Annual greenhouse gas emissions from a rice paddy with different water-nitrogen management strategies in Central China - Jianling Li; Yu’e Li; Yunfan Wan; Bin Wang; Weiwei Cai; Xiaobo Qin; Zhihua Zhou; Xingyu Wang; Jianing Yuan; Qi Deng (Soil and Tillage Research, 2024)

A level IV fugacity-based multimedia model based on steady-state particle/gas partitioning theory and its application to study the spatio-temporal trends of PBDEs in atmosphere of northeast China - Meng Qin; Wan-Li Ma; Pu-Fei Yang; Wen-Long Li; Lei Wang; Li-Li Shi; Li Li; Yi-Fan Li (Science of The Total Environment, 2024)

Effect of municipal sludge-based biochar produced at different pyrolysis temperatures on humification and oxytetracycline degradation of pig manure composting - Changqing Liu; Haimin Li; Ji-Qin Ni; Guihua Zhuo; Wan Chen; Yuyi Zheng; Guangyin Zhen (Science of The Total Environment, 2024)

E. coli phage transport in porous media: Response to colloid types and water saturation - Wenjing Zhang; Shuxin Li; Kaichao Zhao; Juanfen Chai; Bo Wan; Yunqi Qin; Huan Huan; Simiao Sun; Yuesuo Yang; Muhammad Yousuf Jat Baloch (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

A VGGNet-based correction for satellite altimetry-derived gravity anomalies to improve the accuracy of bathymetry to depths of 6 500 m - Xiaolun Chen; Xiaowen Luo; Ziyin Wu; Xiaoming Qin; Jihong Shang; Huajun Xu; Bin Li; Mingwei Wang; Hongyang Wan (Acta Oceanologica Sinica, 2024)

Interfacial adsorption of gold nanoparticles on arsenian pyrite: New insights for the transport and deposition of gold nanoparticles - Xin Nie; Quan Wan; Michael F. Hochella; Suxing Luo; Meizhi Yang; Shanshan Li; Yuhong Fu; Ping Zeng; Zonghua Qin; Wenbin Yu (Chemical Geology, 2023)

Proteomic characteristics of six snake venoms from the Viperidae and Elapidae families in China and their relation to local tissue necrosis - Wan-Gang Qin; Zhan-Peng Zhuo; Hao Hu; Mimi Lay; Qian-Qin Li; Jun-Ting Huang; Liang-Bo Zeng; Zi-Jing Liang; Fei Long; Qing Liang (Toxicon, 2023)

Neoproterozoic tectonic transition from subduction to back-arc extension along the western Yangtze Block, South China: Petrological evidence of Nb-enriched basalts and arc-type intrusive rocks - Yu Zhu; Shao-cong Lai; Wan-li Xie; Jiang-feng Qin; Ren-zhi Zhu; Shao-wei Zhao; Min Liu; Fang-yi Zhang; Ze-zhong Zhang; Hang Yang (Gondwana Research, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

miR-218-5p and miR-320a-5p as Biomarkers for Brain Disorders: Focus on the Major Depressive Disorder and Parkinson’s Disease - Zhirong Wan; Madiha Rasheed; Yumeng Li; Qin Li; Peifu Wang; Jilai Li; Zixuan Chen; Jichen Du; Yulin Deng (Molecular Neurobiology, 2023)

Applicability of core-shell SiO2 microspheres with a high TiO2 loading as stationary phase for HPLC - Dian Wang; Xiang Wan; Jiafei Wang; Debby Mangelings; Qin Xu; Fazhi Xie; Xianhuai Huang; Weihua Li; Han Xuan; Wensheng Zou; Qishu Qu (Analytica Chimica Acta, 2023)

Nrf2 protects against methamphetamine-induced nephrotoxicity by mitigating oxidative stress and autophagy in mice - Wenjuan Dong; Jia Wan; Hao Yu; Baoyu Shen; Genmeng Yang; Qianyun Nie; Yan Tian; Lixiang Qin; Chunhui Song; Bingzheng Chen; Lihua Li; Shijun Hong (Toxicology Letters, 2023)

An extremely safe and flexible zinc-ion hybrid supercapacitor based on a scalable, thin and high-performance hierarchical structured gel electrolyte - Shangdong Qin; Chao Wan; Mingwei Xu; Jun Huang; Kui Chen; Qinqin Xu; Shizhao Li; Fazhi Zhang; Yuanlong Guo; Yang You; Haibo Xie (Chemical Engineering Journal, 2023)

Novel biphasic mechanism of the canonical Wnt signalling component PYGO2 promotes cardiomyocyte differentiation from hUC-MSCs - Yan Shi; Bin Qin; Xiongwei Fan; Yongqing Li; Yuequn Wang; Wuzhou Yuan; Zhigang Jiang; Ping Zhu; Jimei Chen; Yu Chen; Fang Li; Yongqi Wan; et al. (Cell and Tissue Research, 2023)
Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) are used to regenerate the myocardium during cardiac repair after myocardial infarction. However, the regulatory mechanism underlying their ability to form mesodermal cells and differentiate into cardiomyocytes remains unclear. Here, we established a human-derived MSCs line isolated from healthy umbilical cords and established a cell model of the natural state to examine the differentiation of hUC-MSCs into cardiomyocytes. Quantitative RT-PCR, western blotting, immunofluorescence, flow cytometry, RNA Seq, and inhibitors of canonical Wnt signalling were used to detect the germ-layer markers T and MIXL1 ; the markers of cardiac progenitor cells MESP1 , GATA4 , and NKX2.5 and the cardiomyocyte-marker cTnT to identify the molecular mechanism associated with PYGO2, a key component of the canonical Wnt signalling pathway that regulates the formation of cardiomyocyte-like cells. We demonstrated that PYGO2 promotes the formation of mesodermal-like cells and their differentiation into cardiomyocytes through the hUC-MSC-dependent canonical Wnt signalling by promoting the early-stage entry of β-catenin into the nucleus. Surprisingly, PYGO2 did not alter the expression of the canonical-Wnt, NOTCH, or BMP signalling pathways during the middle–late stages. In contrast, PI3K-Akt signalling promoted hUC-MSCs formation and their differentiation into cardiomyocyte-like cells. To the best of our knowledge, this is the first study to demonstrate that PYGO2 uses a biphasic mechanism to promote cardiomyocyte formation from hUC-MSCs.

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Precisely mapping a major QTL for grain weight on chromosome 5B of the founder parent Chuanmai42 in the wheat-growing region of southwestern China - Meijin Ye; Hongshen Wan; Wuyun Yang; Zehou Liu; Qin Wang; Ning Yang; Hai Long; Guangbing Deng; Yumin Yang; Hong Feng; Yonghong Zhou; Cairong Yang; et al. (Theoretical and Applied Genetics, 2023)

Total Nitrogen and Total Phosphorus Pollution Reshaped the Relationship Between Water Supply and Demand in the Huaihe River Watershed, China - Yan Lu; Lyuyi Liu; Fen Qin; Jiayao Wang; Jianzhong Liu; Yingjie Li; Luwen Wan (Chinese Geographical Science, 2023)

Enhanced selective separation of vanadium(V) and chromium(VI) using the CeO2 nanorod containing oxygen vacancies - Ruixi Lin; Jiarong Li; Xuequan Jing; Meina Guo; Guoqing Ren; Haonan Qin; Zhangwei Yao; Yinhua Wan; Weijie Song; Huifeng Zeng; Feifei Yang; Da Zhao; et al. (Environmental Science and Pollution Research, 2023)

Exploring the contributions of major emission sources to PM2.5 and attributable health burdens in China - Yong Li; Liyang Xue; Yan Tao; Yidu Li; Yancong Wu; Qin Liao; Junyi Wan; Yun Bai (Environmental Pollution, 2023)

Soil warming decreases carbon availability and reduces metabolic functions of bacteria - Pingxing Wan; Feng Zhang; Kaiping Zhang; Yufei Li; Rongzhu Qin; Jianjun Yang; Chao Fang; Yakov Kuzyakov; Shiqing Li; Feng-Min Li (CATENA, 2023)

Power to biogas upgrading: Effects of different H2/CO2 ratios on products and microbial communities in anaerobic fermentation system - Zhijie Xie; Siyuan Huang; Yuqin Wan; Fang Deng; Qin Cao; Xiaofeng Liu; Dong Li (Science of The Total Environment, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Design of novel double-layer coated ammonium polyphosphate and its application in flame retardant thermoplastic polyurethanes - Mei Wan; Congling Shi; Xiaodong Qian; Yueping Qin; Jingyun Jing; Honglei Che; Fei Ren; Jian Li; Bin Yu; Keqing Zhou (Chemical Engineering Journal, 2023)

Studies of interspecific backcross between hybrids of (Crassostrea angulata ♀ × C. gigas ♂) and their two parental species - Gongpengyang Shi; Yanping Qin; Weitao Wan; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Yunqing Li; Yinyin Zhou; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

A novel monoclonal antibody efficiently blocks the infection of duck adenovirus 3 by targeting Fiber-2 - Yun Lin; Wenyuan Zhang; Jing Xie; Quan Xie; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Jianqiang Ye (Veterinary Microbiology, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

Rice straw application improves yield marginally and increases carbon footprint of double cropping paddy rice (Oryza sativa L.) - Xiaobo Qin; Yanhong Lu; Yunfan Wan; Bin Wang; Jun Nie; Yu’e Li; Yulin Liao (Field Crops Research, 2023)

S100A4-dependent glycolysis promotes lymphatic vessel sprouting in tumor - Anqi Li; Linyu Zhu; Ningjing Lei; Jiajia Wan; Xixi Duan; Shuangqing Liu; Yanru Cheng; Ming Wang; Zhuoyu Gu; Huilei Zhang; Yueyue Bai; Li Zhang; et al. (Angiogenesis, 2023)

Comparative analysis of growth, survival and sex proportion among tetraploid-based autotriploid (Crassostrea gigas and C. angulata) and their allotriploid oysters - Yanping Qin; Gongpengyang Shi; Weitao Wan; Shengyong Li; Yunqing Li; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

Feasibility of interspecific hybridization between Iwagaki oyster, Crassostrea nippona and Portuguese oyster, Crassostrea angulata - Shengyong Li; Yanping Qin; Gongpengyang Shi; Weitao Wan; Qingliang Liao; Haitao Ma; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2023)

Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2023)

The optimum cooking time: A possible key index for predicting the deterioration of fresh white-salted noodle - Qin Guo; Yun-ting Li; Jia-hui Cai; Cheng-wan Ren; Muhammad Adil Farooq; Bin Xu (Journal of Cereal Science, 2023)

Enhanced formation kinetics of hydrates using 1,3-dioxolane, l-leucine, and β-cyclodextrin - Yue Qin; Ruixin Bao; Li Zhou; Xu Yang; Chaoguang Liu; Wenfei Wan; Yong Chen; You Guo (Fuel, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

In vitro toxicity assessment of haloacetamides via a toxicogenomics assay - Dong Li; Wen Cheng; Jiehui Ren; Lu Qin; Xing Zheng; Tian Wan; Min Wang (Environmental Toxicology and Pharmacology, 2023)

Developing membrane reactors with suspended polyphthalocyanine nanoplatelets for upscaling syntheses of protein-polymer bioconjugates - Wen Fang Wei; Wan Lin Guo; Min Jian; Liu Shu Qin; Xue Li; Tao Cai (Chemical Engineering Journal, 2023)

Design and efficacy of all-in-one sandwich-like multifunctional platform for drug delivery - Bo Zhang; Yumei Qin; Yanyan Li; Yu Wang; Huining Wan; Xiyu Liu; Xiaoqin Hu; Yongqi An; Hao Zhang; Li Yang; Rifang Luo; Yunbing Wang (Chemical Engineering Journal, 2023)

Ni(OH)2 clusters decorated NiTiO3 Z-scheme heterojunctions with strong O2 activation and robust interfacial built-in electric field for efficient NO photo-oxidation - Guojun Li; Zheng Lian; Zhengwei Wan; Zhinian Liu; Jingwen Qian; Yue Deng; Shule Zhang; Qin Zhong (Chemical Engineering Journal, 2023)

Functional characterization of powdery mildew resistance-related genes HbSGT1a and HbSGT1b in Hevea brasiliensis Muell. Arg. - Meng Wang; Huaxing Xiao; Xiaona Li; Sanlian Wan; Ye Yang; Haiyang Yu; Yu Zhang; Bi Qin (European Journal of Plant Pathology, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

The assessment and source apportionment of metals in the water-level fluctuation zone of the upper reaches Yangtze mainstream - Pengcheng Wang; Li Ma; Qiuyun Huang; Hai Yu; Ying Liu; Weiwei Jiang; Juan Wan; Qin Wang; Henglin Xiao (Journal of Soils and Sediments, 2022)

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Geochemical characteristics and growth suitability assessment of Scutellaria baicalensis Georgi in the Earth’s critical zone of North China - Xia Li; Xiao-feng Wei; Jin Wu; Zhi-qiang Yin; Li-qin Wan; Hou-yun Sun; Yong-long An (Journal of Mountain Science, 2022)

Spatial distribution patterns and sources for potential toxic elements in soil in the Daxing District, Beijing, China - Yong-long An; Yong Huang; Zhi-qiang Yin; Xiu-lan Yin; Xia Li; Li-qin Wan; Ai-fang Jin; Wen-juan Li; Hai Shao; Li-li Chen (Arabian Journal of Geosciences, 2022)

Handelin extends lifespan and healthspan of Caenorhabditis elegans by reducing ROS generation and improving motor function - Huijie Zhang; Jiawei Qin; Xinqiang Lan; Weirong Zeng; Jing Zhou; Tian-E Huang; Wan-Li Xiao; Qi-Quan Wang; Sujiao Sun; Weiting Su; Wenhui Nie; Shan Yang; et al. (Biogerontology, 2022)

Concentration determination of gold nanoparticles by flame atomic absorption spectrophotometry - Yuhong Fu; Quan Wan; Zonghua Qin; Shanshan Li; Sen Li; Ji Wang; Wei Zhang (Acta Geochimica, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

New geochronological and geochemical data of the Longsheng mafic-ultramafic suite in northern Guangxi, China, and their implications in Rodinia breakup - Yizhi Liu; Ya Qin; Zuohai Feng; Saisai Li; Lei Wan; Chunzeng Wang (Arabian Journal of Geosciences, 2021)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Genetic diversity analysis reveals new badnaviruses infecting banana in South China - Xue-Qin Rao; Zi-Lin Wu; Wan Wang; Lin Zhou; Jie Sun; Hua-Ping Li (Journal of Plant Pathology, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Evolutionary history of the heat shock protein 90 (Hsp90) family of 43 plants and characterization of Hsp90s in Solanum tuberosum - Wan Li; Yue Chen; Minghui Ye; Dongdong Wang; Qin Chen (Molecular Biology Reports, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Correction to: Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2020)

The effect of pH on the sorption of gold nanoparticles on illite - Yuhong Fu; Quan Wan; Zonghua Qin; Xin Nie; Wenbin Yu; Shanshan Li (Acta Geochimica, 2020)

Synthesis and plant growth regulatory activities of 2′,3′-PhABA and iso-2′,3′-PhABA esters - Chuan Wan; Jiaqi Li; Fenghai Zhao; Dongyan Yang; Chuanliang Che; Shanshan Ding; Yimin Hu; Yumei Xiao; Zhaohai Qin (Molecular Diversity, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Identification and Analysis of Vulnerability in Traffic-Intensive Areas of Water Transportation Systems - Yong-jun Chen; Qing Liu; Cheng-peng Wan; Qin Li; Peng-wei Yuan (Journal of Marine Science and Engineering, 2019)
Water transportation accidents have occurred frequently in recent years. In order to improve the emergency response capability of water transportation systems under traffic-intensive conditions, this paper identifies and analyzes the vulnerability in traffic-intensive areas of water transportation systems. Firstly, the vulnerability identification model was constructed based on the analysis of characteristics and the vulnerability-influencing factors of water transportation systems. The newly proposed model is composed of three parts including the DEMATEL (Decision Making Trial and Evaluation Laboratory) method, ISM (interpretative structural modeling) model, and AHP (Analytic Hierarchy Process)–entropy weight method. Finally, a case study of the Yangtze River was conducted to test the logicality and feasibility of the proposed model. The research results reveal that traffic flow density, ship traffic, tides, fog, and bad weather are the key factors affecting the vulnerability of water transportation in traffic-intensive areas of the Yangtze River estuary. However, the influence of navigation aid configuration, berth, anchorage, and obstruction on the system vulnerability is relatively lower. The findings of this study can provide helpful references for maritime administration authorities on the management of water transportation safety.

Transcriptomic responses of the marine cyanobacterium Prochlorococcus to viral lysis products - Xiaoting Fang; Yaxin Liu; Yao Zhao; Yue Chen; Riyue Liu; Qi‐Long Qin; Gang Li; Yu‐Zhong Zhang; Wan Chan; Wolfgang R. Hess; Qinglu Zeng (Environmental Microbiology, 2019)
Summary Viral infection of marine phytoplankton releases a variety of dissolved organic matter (DOM). The impact of viral DOM (vDOM) on the uninfected co‐occurring phytoplankton remains largely unknown. Here, we conducted transcriptomic analyses to study the effects of vDOM on the cyanobacterium Prochlorococcus , which is the most abundant photosynthetic organism on Earth. Using Prochlorococcus MIT9313, we showed that its growth was not affected by vDOM, but many tRNAs increased in abundance. We tested tRNA‐gly and found that its abundance increased upon addition of glycine. The decreased transcript abundances of N metabolism genes also suggested that Prochlorococcus responded to organic N compounds in vDOM. Addition of vDOM to Prochlorococcus reduced the maximum photochemical efficiency of photosystem II and CO 2 fixation while increasing its respiration rate, consistent with differentially abundant transcripts related to photosynthesis and respiration. One of the highest positive fold‐changes was observed for the 6S RNA, a noncoding RNA functioning as a global transcriptional regulator in bacteria. The high level of 6S RNA might be responsible for some of the observed transcriptional responses. Taken together, our results revealed the transcriptional regulation of Prochlorococcus in response to viral lysis products and suggested its metabolic potential to utilize organic N compounds.

Limb Remote Ischemic Preconditioning Reduces Repeated Ketamine Exposure-Induced Adverse Effects in the Developing Brain of Rats - Ying Liu; An Qi Li; Wan Ma; Yu Bo Gao; Li Qin Deng; Chun Zhang; Jin Hai Meng (Journal of Molecular Neuroscience, 2019)

Non-invasive Vagus Nerve Stimulation Protects Against Cerebral Ischemia/Reperfusion Injury and Promotes Microglial M2 Polarization Via Interleukin-17A Inhibition - Xiao-Ping Zhao; Yuan Zhao; Xiao-Ya Qin; Li-Yuan Wan; Xiao-Xuan Fan (Journal of Molecular Neuroscience, 2019)

Statistical landslide susceptibility assessment in a dynamic environment: A case study for Lanzhou City, Gansu Province, NW China - Jewgenij Torizin; Li-chao Wang; Michael Fuchs; Bin Tong; Dirk Balzer; Li-qin Wan; Dirk Kuhn; Ang Li; Liang Chen (Journal of Mountain Science, 2018)

Long-term (≥20 years) application of fertilizers and straw return enhances soil carbon storage: a meta-analysis - Yu’e Li; Shengwei Shi; Muhammad Ahmed Waqas; Xiaoxia Zhou; Jianling Li; Yunfan Wan; Xiaobo Qin; Qingzhu Gao; Shuo Liu; Andreas Wilkes (Mitigation and Adaptation Strategies for Global Change, 2018)

Human amylin induces CD4+Foxp3+ regulatory T cells in the protection from autoimmune diabetes - Xiao-xi Zhang; Yong-chao Qiao; Wan Li; Xia Zou; Yin-ling Chen; Jian Shen; Qin-yuan Liao; Qiu-jin Zhang; Lan He; Hai-lu Zhao (Immunologic Research, 2018)

Variations of Laohugou Glacier No. 12 in the western Qilian Mountains, China, from 1957 to 2015 - Yu-shuo Liu; Xiang Qin; Ji-zu Chen; Zhen-lin Li; Jing Wang; Wen-tao Du; Wan-qin Guo (Journal of Mountain Science, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Risk alleles for IgA nephropathy-associated SNPs conferred completely opposite effects to idiopathic membranous nephropathy in Chinese Han - Xiaosong Qin; Chen Wang; Guanting Lu; Mengle Peng; Guixue Cheng; Hongquan Zhu; Yun Cao; Jianhua Liu; Yuzhong Li; Hong Cai; Funing Yang; Yanhong Liu; et al. (Immunologic Research, 2017)

Establishment of a somatic embryo regeneration system and expression analysis of somatic embryogenesis-related genes in Chinese chestnut (Castanea mollissima Blume) - Dan Lu; Wei Wei; Wan Zhou; Linda D. McGuigan; Fei-yang Ji; Xiao Li; Yu Xing; Qing Zhang; Ke-feng Fang; Qing-qin Cao; Ling Qin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Protective mechanisms of hypaconitine and glycyrrhetinic acid compatibility in oxygen and glucose deprivation injury - Li-qin Wang; Yu He; Hao-fang Wan; Hui-fen Zhou; Jie-hong Yang; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Novel avian leukosis viruses from domestic chicken breeds in mainland China - Hongxia Shao; Lin Wang; Jianjun Sang; Tuofan Li; Yuelong Liu; Zhimin Wan; Kun Qian; Aijian Qin; Jianqiang Ye (Archives of Virology, 2017)

Hydrogen Sulfide Promotes Wheat Grain Germination Under Cadmium Stress - Zhong-Qin Huang; Shao-Can Ye; Lan-Ying Hu; Kang-Di Hu; Hong Yan; Wan-Jie Li; Hao Jiao; Hua Zhang (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Glacier change in the western Nyainqentanglha Range, Tibetan Plateau using historical maps and Landsat imagery: 1970-2014 - Kun-peng Wu; Shi-yin Liu; Wan-qin Guo; Jun-feng Wei; Jun-li Xu; Wei-jia Bao; Xiao-jun Yao (Journal of Mountain Science, 2016)

A public Cloud-based China’s Landslide Inventory Database (CsLID): development, zone, and spatiotemporal analysis for significant historical events, 1949-2011 - Wei-yue Li; Chun Liu; Yang Hong; Xin-hua Zhang; Zhan-ming Wan; Manabendra Saharia; Wei-wei Sun; Dong-jing Yao; Wen Chen; Sheng Chen; Xiu-qin Yang; Yue Yue (Journal of Mountain Science, 2016)

Glacier changes since the early 1960s, eastern Pamir, China - Zhen Zhang; Jun-li Xu; Shi-yin Liu; Wan-qin Guo; Jun-feng Wei; Tong Feng (Journal of Mountain Science, 2016)

Long-distance transport of cadmium from roots to leaves of Solanum melongena - Qin Qin; Xuemei Li; Jie Zhuang; Liping Weng; Wan Liu; Peidong Tai (Ecotoxicology, 2015)

Circulating 25-hydroxyvitamin D and risk of lung cancer: a dose–response meta-analysis - Guo-Chong Chen; Zeng-Li Zhang; Zhongxiao Wan; Ling Wang; Peter Weber; Manfred Eggersdorfer; Li-Qiang Qin; Weiguo Zhang (Cancer Causes & Control, 2015)

Mass loss from glaciers in the Chinese Altai Mountains between 1959 and 2008 revealed based on historical maps, SRTM, and ASTER images - Jun-feng Wei; Shi-yin Liu; Jun-li Xu; Wan-qin Guo; Wei-jia Bao; Dong-hui Shangguan; Zong-li Jiang (Journal of Mountain Science, 2015)

Greenhouse gas emissions from agricultural irrigation in China - Xiaoxia Zou; Yu’e Li; Kuo Li; Roger Cremades; Qingzhu Gao; Yunfan Wan; Xiaobo Qin (Mitigation and Adaptation Strategies for Global Change, 2015)

Antibacterial mechanisms of methyl gallate against Ralstonia solanacearum - Wan-Wan Fan; Gao-Qing Yuan; Qi-Qin Li; Wei Lin (Australasian Plant Pathology, 2014)

Evaluation of predation abilities of Blattisocius dolichus (Acari: Blattisociidae) on a plant-parasitic nematode, Radopholus similis (Tylenchida: Pratylenchidae) - Yong Liang Chen; Chun Ling Xu; Xue Nong Xu; Hui Xie; Bao Xin Zhang; Hou Guo Qin; Wan Qin Zhou; Dun Song Li (Experimental and Applied Acarology, 2013)

Effects of topography and human activity on the net primary productivity (NPP) of alpine grassland in northern Tibet from 1981 to 2004 - Qingzhu Gao; Yunfan Wan; Yue Li; Yaqi Guo; Ganjurjav; Xioabo Qin; Wangzha Jiangcun; Baoshan Wang (International Journal of Remote Sensing, 2013)

Two non-allelic nuclear genes restore fertility in a gametophytic pattern and enhance abiotic stress tolerance in the hybrid rice plant - Wenchao Huang; Jun Hu; Changchun Yu; Qi Huang; Lei Wan; Lili Wang; Xiaojian Qin; Yanxiao Ji; Renshan Zhu; Shaoqing Li; Yingguo Zhu (Theoretical and Applied Genetics, 2012)

N and O isotopes and the ore-forming mechanism of nitrate deposits in the Turpan-Hami Basin, Xinjiang, China - Yan Qin; YanHe Li; Feng Liu; KeJun Hou; DeFang Wan; Cheng Zhang (Science China Earth Sciences, 2012)

Primary dolostone formation related to mantle-originated exhalative hydrothermal activities, Permian Yuejingou section, Santanghu area, Xinjiang, NW China - YiQun Liu; Xin Jiao; Hong Li; MingSheng Yuan; Wan Yang; XiaoHu Zhou; Hao Liang; DingWu Zhou; ChaoYang Zheng; Qin Sun; ShuangShuang Wang (Science China Earth Sciences, 2012)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Identification and characterization of a novel capsid protein encoded by Singapore grouper iridovirus ORF038L - Qing Jiao Wan; Jie Gong; Xiao Hong Huang; You Hua Huang; Sheng Zhou; Zheng Liang Ou-Yang; Jian Hao Cao; Li Li Ye; Qi Wei Qin (Archives of Virology, 2010)

Dynamics of alpine grassland NPP and its response to climate change in Northern Tibet - Qingzhu Gao; Yue Li; Yunfan Wan; Xiaobo Qin; Wangzha Jiangcun; Yinghui Liu (Climatic Change, 2009)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Antitumor activities of D-glucosamine and its derivatives - Li Zhang; Wan-shun Liu; Bao-qin Han; Yan-fei Peng; Dong-feng Wang (Journal of Zhejiang University-SCIENCE B, 2006)